Students’ Speaking Practice: Problems and Solutions - Anita Anita; Siti Sadiah; Kheryadi Kheryadi; Hasunah Hasunah; Yosman Ahmadi; Khairil Razali (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
The study focused on identifing students’ problems in practicing English speaking, investigating students’ strategy to solve their speaking problems, and finding out the strategies used by teachers to trigger students to speak and practice their English. The study employed mixed method. It was conducted at English Education Department, Faculty of Education and Teacher Training, UIN Sultan Maulana Hasanuddin Banten. The data were obtained through questionnaire and interview. The analysis showed that most of students have got difficulty in putting the words into the correct position and constructing the correct sentences when they want to speak up. The most strategy used by the students to solve their problems on speaking skill was by utilizing the medium of you tube to enhace their vocabulary and pronunciation. The strategy done by the lecturers to motivate the students to speak English was to remind the students to speak up eventhough the grammar is not correct.